Model-based prediction, fault estimation and optimal control: application on wine fermentation and time-delay systems - Lima, Bruno Martins (2024)
Dissertação (mestrado) - Universidade Federal de Santa Catarina, Centro Tecnológico, Programa de Pós-Graduação em Engenharia de Automação e Sistemas, Florianópolis, 2024.